Production and persistence of Mediterranean perennial grasses under contrasting climatic scenarios - Poirier M.; Durand J.L.; Volaire F. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
In the current context of increasing droughts due to climate change, this study analyzed the effects of a range of severe summer water deficits (-329 to -710 mm) and summer high temperatures (+3 and +6°C than ambient temperatures for 2-3 weeks) on the persistence and production of perennial forage grasses. We compared a Mediterranean cultivar (cv) of cocksfoot (Dactylis glomerata L., cv Medly) and of tall fescue (Festuca arundinacea Schreb, cv. Centurion), in both a Mediterranean and a temperate site in France. The results show that (1) the annual production was variable but reduced on average by 40% along the range of tested water deficits; (2) the thresholds of significant increased mortality occurred at around 560 mm of water deficit; (3) deeper water uptake can be associated with the greater persistence of tall fescue at high water deficit and (4) an after-effect of summer water deficits resulted in an increase of frost sensitivity especially for cocksfoot. To cope with climate change, breeding programs for Mediterranean cultivars should aim to improve both frost tolerance and drought survival through increased summer dormancy.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)